Academician: netizens' low approval rating for 15 our of 18 Dayak ministers, deputy ministers "should serve as wake up call" - DayakDaily Team (2025)
A simple, random survey among netizens on how they viewed the performance of their ministers, deputy ministers in the Madani government.